Faktor Pengaruh Manajemen Material terhadap Kinerja Pelaksanaan pada Proyek Konstruksi - Siti Fadilah Angkaleda; Arfan Usman Sumaga; Moh Yusuf Tuloli (Transbahasa, 2025)
Rapid population growth increases need in various sectors, including infrastructure development. In Indonesia, infrastructure development is expected to improve people's welfare, although it often contributes to significant environmental changes, from the construction to operational stages. Construction projects use limited natural resources and have negative impacts on the environment, such as reduced open space and pollution from heavy equipment and transportation. To reduce this negative impact, it is necessary to apply the concept of environmentally friendly development, namely green construction. This concept emphasizes energy efficiency, use of environmentally friendly materials, good water management and work safety. This research aims to analyze the application of green construction criteria in the implementation of construction development in Gorontalo City and identify the most dominant criteria applied. The data collection method uses a survey by distributing questionnaires to construction actors. Data analysis uses descriptive statistical methods and a ranking system. The research results show that water and energy efficiency are the most dominant criteria applied, with a percentage of 80%, especially in maximizing the use of sunlight to reduce electricity use.